2007
DOI: 10.1146/annurev.psych.58.110405.085701
|View full text |Cite
|
Sign up to set email alerts
|

The Close Relationships of Lesbians and Gay Men

Abstract: This article reviews empirical studies of same-sex couples in the United States, highlighting consistent findings, drawing comparisons to heterosexual couples, and noting gaps in available research. U.S. Census data indicate that there were more than 600,000 same-sex couples living together in 2000. Research about relationship formation, the division of household labor, power, satisfaction, sexuality, conflict, commitment, and relationship stability is presented. Next, we highlight three recent research topics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
356
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(395 citation statements)
references
References 82 publications
29
356
0
10
Order By: Relevance
“…And indeed, contrary to many stereotypical notions about how different (or dysfunctional) same-sex relationships would be, research generally indicated that they appear to operate in largely the same manner as their heterosexual counterparts, with the same types of factors generally associated with relationship satisfaction (e.g., Kurdek, 2004; see review in Peplau & Fingerhut, 2007). Moreover, where differences have been found to exist, they may be in a positive direction, such as a greater emphasis on equality within same-sex relationships and more effective conflict resolution behaviors (e.g., Gottman et al, 2003;Kurdek, 2005).…”
Section: Through a New Lensmentioning
confidence: 90%
“…And indeed, contrary to many stereotypical notions about how different (or dysfunctional) same-sex relationships would be, research generally indicated that they appear to operate in largely the same manner as their heterosexual counterparts, with the same types of factors generally associated with relationship satisfaction (e.g., Kurdek, 2004; see review in Peplau & Fingerhut, 2007). Moreover, where differences have been found to exist, they may be in a positive direction, such as a greater emphasis on equality within same-sex relationships and more effective conflict resolution behaviors (e.g., Gottman et al, 2003;Kurdek, 2005).…”
Section: Through a New Lensmentioning
confidence: 90%
“…However, the precise nature of bisexuals' intimate relationships is not well documented and, for example, whether bisexuals' greater victimisation from intimate partners occurs when they are in a same-sex or an opposite-sex relationship is uncertain from the research. Many bisexuals are in heterosexual relationships (Buxton, 2004) and although there is some research on the close relationships of lesbians and gay men (Peplau & Fingerhut, 2007) there is currently little research on bisexual experiences in heterosexual relationships. Importantly, that which does exist does not demonstrate that such relationships are more likely to involve violence (Wolf, 1985).…”
Section: Previous Researchmentioning
confidence: 99%
“…Participants who were avoidant style in their romantic attachment reported more Ludus love style (i.e., game-playing) compared to individuals with the other two romantic attachment styles (i.e., secure or anxious ambivalent). Peplau and Fingerhut (2007) Researchers have demonstrated that many negative social stereotypes towards gays and lesbians romantic relationships are not accurate. For example, the media have stereotyped these types of relationships as unstable and portray gays and lesbians as unhappy in their romantic relationships.…”
Section: Romantic Attachment Stylesmentioning
confidence: 99%
“…Another social stereotype is that these gay, lesbian, and bisexual individuals are unable to establish intimate, passionate kinds of love and relationships compared to heterosexual individuals despite the similarities in heterosexual couples and gay and lesbian couples in their romantic relationships in terms of satisfaction and love experiences in the research. Cultural stereotypes (i.e., "butch versus "fem") of gay, lesbian, and bisexual individuals as mimicking "husband" and "wife" roles have also been projected in the mainstream culture, which are not accurate (Peplau and Fingerhut, 2007); gays and lesbians divide the roles by personal interests and area of expertise in terms of household labor (Peplau and Fingerhut, 2007).…”
Section: Romantic Attachment Stylesmentioning
confidence: 99%
See 1 more Smart Citation